2018
DOI: 10.2147/idr.s174913
|View full text |Cite
|
Sign up to set email alerts
|

Platelet reactivity in diabetic patients with invasive <em>Klebsiella pneumoniae</em> liver abscess syndrome

Abstract: ObjectivePlatelets catalyze the development of hyperinflammation and microthrombosis and contribute to increases in accumulation of circulating platelet-leukocyte complex, the key event in the development of disseminated infection.Subjects and methodsTo determine the relationships of platelet activity in diabetic patients with invasive Klebsiella pneumoniae liver abscess syndrome (IKLAS), a total of 175 diabetic patients with community-acquired Klebsiella pneumoniae (KP) bacteremia were included in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The most common routes of infection are biliary tract infection and hematogenous infection [ 19 ]. The clinical manifestations of patients with liver abscess include fever, nausea/vomiting, chills, liver pain, elevated white blood cell count, with or without hepatomegaly, and fatigue [ 20 , 21 ]. Currently, surgical treatment is advocated in clinical practice for attenuating the condition in which the puncture and drainage technique is widely used.…”
Section: Discussionmentioning
confidence: 99%
“…The most common routes of infection are biliary tract infection and hematogenous infection [ 19 ]. The clinical manifestations of patients with liver abscess include fever, nausea/vomiting, chills, liver pain, elevated white blood cell count, with or without hepatomegaly, and fatigue [ 20 , 21 ]. Currently, surgical treatment is advocated in clinical practice for attenuating the condition in which the puncture and drainage technique is widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin has been reported to inhibit the production of KP CPS, which is important to its virulence because of its anti-phagocytic effect against macrophages and neutrophils 12,21 . Plateletmonocyte aggregation is also involved in the pathogenesis of KP-PLA in diabetic patients, which was shown to be decreased by aspirin 22 . www.nature.com/scientificreports/ In addition to aspirin use, our study revealed that taking clopidogrel reduced the risk of KP-PLA.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients admitted to KCGMH between January 1, 2013 and December 31, 2016 with community-acquired mono-microbial bacteremia caused by KP were included to determine the patients with KP-PLA recurrence 21 . PLA recurrence was defined as having a typical clinical presentation, with new imaging findings of abscess recurrence after the first episode of abscess had fully resolved.…”
Section: Methodsmentioning
confidence: 99%